Natural history of HPV in men: what remains to be learnt? - Baggio, Maria Luiza; Galan, Lenice; Villa, Luisa L.; Silva, Roberto José C.; Gomes, Elimar (Brazilian Journal of Sexually Transmitted Diseases, 2010)
It is known that human papillomavirus (HPV) contributes to the occurrence of cancer of the anal, penile, oropharynx and genital and anal warts in men. Furthermore, HPV infection significantly influences the infection and subsequent dysplasia and invasive cervical cancer in women. Cohort studies are contributing to the knowledge of the natural history of these infections in men, especially in the genital and anal regions; in addition, the impact of coinfection with HIV, and studies on the role of circumcision are fundamental in defining strategies for prevention and control of infections and diseases caused by HPV in men and hence women.